Liquidity shocks and asset price boom/bust cycles - Ramón Adalid; Carsten Detken (European Central Bank (ECB), 2007)
We provide systematic evidence for the association of liquidity shocks and aggregate asset prices during mechanically identified asset price boom/bust episodes for 18 OECD countries since the 1970s, while taking care of the endogeneity of money and credit. Our derivation of liquidity shocks allows for frequent shifts in velocity as they are derived as structural shocks from VARs in growth rates. Residential property price developments and money growth shocks accumulated over the boom periods are able to well explain the depth of post-boom recessions. We further suggest that liquidity shocks are a driving factor for real estate prices during boom episodes. During normal times however, the relative predictive power of liquidity shocks seems to shift from asset price inflation to consumer price inflation. The results only hold for broad money growth based liquidity shocks and not for private credit growth shocks.
Keywords: C33; E41; E51; E58; 330; asset price booms; Liquidity shocks; monetary policy; money and credit aggregates; real estate prices; role of money; Spekulationsblase; Liquiditätseffekt; Geldpolitik; OECD-Staaten